Breast cancer-induced immune suppression in the sentinel lymph node is effectively countered by CpG-B in conjunction with inhibition of the JAK2/STAT3 pathway - van Pul, Kim M; Vuylsteke, Ronald J C L M; de Beijer, Monique T A; van de Ven, Rieneke; van den Tol, M Petrousjka; Stockmann, Hein B A C; de Gruijl, Tanja D (Journal for immunotherapy of cancer, 2020)
BackgroundWe previously showed selectively hampered activation of lymph node-resident (LNR) dendritic cell (DC) subsets in the breast cancer (BrC) sentinel lymph node (SLN) to precede a state of profound T cell anergy. Reactivating these DC subsets by intratumoral delivery of the Toll-like receptor-9 (TLR9) agonist CpG-B could potentially offer a promising immune therapeutic strategy to combat this immune suppression and prevent disease spread. Unfortunately, CpG-B can limit its own immune stimulatory activity through direct TLR9-mediated activation of signal transducer and activator of transcription 3 (STAT3), pinpointed as a key regulator of immune suppression in the tumor microenvironment. Here, we have investigated whether in vitro exposure to CpG-B, with or without simultaneous inhibition of STAT3 signaling, could overcome immune suppression in BrC SLN.MethodsImmune modulatory effects of CpG-B (CPG7909) with or without the JAK2/STAT3 inhibitor (STAT3i) AG490 were assessed in ex vivo cultured BrC SLN-derived single-cell suspensions (N=29). Multiparameter flow cytometric analyses were conducted for DC and T cell subset characterization and assessment of (intracellular) cytokine profiles. T cell reactivity against the BrC-associated antigen Mammaglobin-A was determined by means of interferon-γ ELISPOT assay.ResultsAlthough CpG-B alone induced activation of all DC subsets, combined inhibition of the JAK2/STAT3 pathway resulted in superior DC maturation (ie, increased CD83 expression), with most profound activation and maturation of LNR DC subsets. Furthermore, combined CpG-B and JAK2/STAT3 inhibition promoted Th1 skewing by counterbalancing the CpG-induced Th2/regulatory T cell response and significantly enhanced Mammaglobin-A specific T cell reactivity.ConclusionEx vivo immune modulation of the SLN by CpG-B and simultaneous JAK2/STAT3 inhibition can effectively overcome BrC-induced immune suppression by preferential activation of LNR DC, ultimately restoring type 1-mediated antitumor immunity, thereby securing a BrC-specific T cell response. These findings provide a clear rationale for clinical exploration of SLN-immune potentiation through local CpG/STAT3i administration in patients with BrC.